Degradation of Epoxy Adhesive containing Dicyandiamide and Carboxyl-Terminated Butadiene Acrylonitrile Rubber due to Water with Open-faced Specimens. Issue 15 (18th November 2021) - Shimamoto, K.; Batorova, S.; Houjou, K.; Akiyama, H.; Sato, C.
ABSTRACT: Adhesive properties are often affected by water. In this study, to clarify the water-resistant properties of a thermosetting epoxy adhesive containing dicyandiamide (DICY) and carboxyl-terminated butadiene acrylonitrile rubber (CTBN), immersion tests of open-faced specimens and bulk specimens in water were performed, and the changes in the properties were investigated in terms of chemistry and mechanical strength. After immersing the open-faced specimens in water, the mechanical strengths were evaluated by two different methods: interfacial cutting method and secondary bonding method. Using both methods, a decrease in strength with immersion time was obtained, and the tendencies of the strength change were found to be very similar for the different evaluation methods. Chemical changes were also evaluated by infrared spectroscopy. Through periodical measurements of the infrared spectra of a fully-cured bulk adhesive specimen during water immersion, the chemical degradation of the epoxy adhesive containing DICY and CTBN was investigated, revealing an association with the change in mechanical strength in which hydrolysis of the cyano groups in DICY and CTBN led to a decrease in strength. Strength recovery experiments were also conducted by drying the specimens after water immersion, determining that the mechanical recovery strength changed with water temperature and immersion time.